2016
DOI: 10.5334/labphon.59
|View full text |Cite
|
Sign up to set email alerts
|

French Speech Segmentation in Liaison Contexts by L1 and L2 Listeners

Abstract: In this study, we consider how native status and signal degradation influence French listeners' segmentation of an incoming speech stream containing liaison, a phonological process that misaligns word and syllable boundaries. In particular, we investigate how both first language (L1) and second language (L2) French listeners compensate for the syllable-word misalignment associated with liaison while segmenting French speech, and whether compensation-for-liaison strategies differ with decreasing signal-to-noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Moreover, it should be noted that the research reviewed thus far has mostly focused on the temporal parameter: the analyses have concerned the duration of the target consonant and, in some cases, of the preceding vowel (very rarely on the VOT: Dejean De La Bâtie 1993; Wauquier-Gravelines 1996). The relative duration of consonants and preceding vowels has also been taken into account (Tremblay & manipulated so as to increase the difference between the two contexts (Shoemaker 2014;Gustafson & Bradlow 2016). Manipulations produced stimuli whose durations were still within the range of variation which was attested in the naturally recorded stimuli, and the studies showed that, when lexical ambiguity is maximal (as in les ailes 'the wings' vs. les zèles 'the zeals'), speakers may rely on such exaggerated acoustic differences to correctly assign the word to either category of vowel-initial or consonant-initial words.…”
Section: The Psycholinguistic Study Of French Liaisonmentioning
confidence: 99%
“…Moreover, it should be noted that the research reviewed thus far has mostly focused on the temporal parameter: the analyses have concerned the duration of the target consonant and, in some cases, of the preceding vowel (very rarely on the VOT: Dejean De La Bâtie 1993; Wauquier-Gravelines 1996). The relative duration of consonants and preceding vowels has also been taken into account (Tremblay & manipulated so as to increase the difference between the two contexts (Shoemaker 2014;Gustafson & Bradlow 2016). Manipulations produced stimuli whose durations were still within the range of variation which was attested in the naturally recorded stimuli, and the studies showed that, when lexical ambiguity is maximal (as in les ailes 'the wings' vs. les zèles 'the zeals'), speakers may rely on such exaggerated acoustic differences to correctly assign the word to either category of vowel-initial or consonant-initial words.…”
Section: The Psycholinguistic Study Of French Liaisonmentioning
confidence: 99%
“…As for L2 listeners, some of this research has focused on how they deal with phonological variation, with mixed results. Advanced learners can range from native-or near-nativelike performance to failure to recover the intended word (Brand and Ernestus, 2018;Darcy, Peperkamp and Dupoux, 2007;Gustafson and Bradlow, 2016;Tremblay, 2011;Tremblay and Spinelli, 2014;Tuinman, Mitterer and Cutler, 2012). Not all phonological variation, though, is harmful for word recognition.…”
Section: Introductionmentioning
confidence: 99%